Platelet in thrombo-inflammation: Unraveling new therapeutic targets - Swati Sharma; Tarun Tyagi; Silvio Antoniak (Frontiers in Immunology, 2022)
In the broad range of human diseases, thrombo-inflammation appears as a clinical manifestation. Clinically, it is well characterized in context of superficial thrombophlebitis that is recognized as thrombosis and inflammation of superficial veins. However, it is more hazardous when developed in the microvasculature of injured/inflamed/infected tissues and organs. Several diseases like sepsis and ischemia-reperfusion can cause formation of microvascular thrombosis subsequently leading to thrombo-inflammation. Thrombo-inflammation can also occur in cases of antiphospholipid syndrome, preeclampsia, sickle cell disease, bacterial and viral infection. One of the major contributors to thrombo-inflammation is the loss of normal anti-thrombotic and anti-inflammatory potential of the endothelial cells of vasculature. This manifest itself in the form of dysregulation of the coagulation pathway and complement system, pathologic platelet activation, and increased recruitment of leukocyte within the microvasculature. The role of platelets in hemostasis and formation of thrombi under pathologic and non-pathologic conditions is well established. Platelets are anucleate cells known for their essential role in primary hemostasis and the coagulation pathway. In recent years, studies provide strong evidence for the critical involvement of platelets in inflammatory processes like acute ischemic stroke, and viral infections like Coronavirus disease 2019 (COVID-19). This has encouraged the researchers to investigate the contribution of platelets in the pathology of various thrombo-inflammatory diseases. The inhibition of platelet surface receptors or their intracellular signaling which mediate initial platelet activation and adhesion might prove to be suitable targets in thrombo-inflammatory disorders. Thus, the present review summarizes the concept and mechanism of platelet signaling and briefly discuss their role in sterile and non-sterile thrombo-inflammation, with the emphasis on role of platelets in COVID-19 induced thrombo-inflammation. The aim of this review is to summarize the recent developments in deciphering the role of the platelets in thrombo-inflammation and discuss their potential as pharmaceutical targets.